Pengaruh Model Pembelajaran RADEC (Read, Answer, Discussion, Explain, and Create) Terhadap Kemampuan Berpikir Kritis Peserta Didik Kelas V pada Pembelajaran IPA SD Inpres Pattallassang - Esti Dwi Amelia; Muh. Erwinto Imran; Anisa Anisa (Journal on Education, 2024)
The aim of this research is to determine the level of critical thinking skills and their influence on the use of the RADEC learning model for class V students in science learning at SD Inpres Pattallassang. This research is a quantitative approach with a type of experimental research with quasi-experimental methods. The population in this study was all students in class V of SD Inpres Pattallassang, totaling 99 students with a sample of class VA as the experimental class and class VB as the control class. The sampling technique used was random sampling. The independent variable in this research is the RADEC learning model, while the dependent variable is the critical thinking ability of class V students in science learning at SD Inpres Pattallassang. The data collection technique uses critical thinking ability tests in the form of essay questions, observation and documentation. The instruments used are cirical thinking ability test instruments and observation sheets. The data analysis techniques used are descriptive statistical analysis, inferential analysis, namely prerequisite testing and hypothesis testing (independent sample t test). Based on the results of hypothesis testing, the Sig (2-tailed) value was 0.035 < 0.05. Thus, it can be concluded that there is a significant influence between the average critical thinking ability of students who use the RADEC learning model and the Problem Based Lerning.